Mixed structured physical exercise program for obese workers: combating sedentary and metabolic risk factors related to metabolism workplace syndrome - Godefroid Kusuayi Mabele; Constant Nkiama Ekisawa; Betty Miangindula; Christophe Delecluse; François Lepira Bompeka; Pierre Akilimali (Turkish Journal of Kinesiology, 2019)
To develop a program of high volume physical exercises, of moderate to high intensity, adapted to the working context of Kinshasa. In a trial study of structured, spontaneous and mixed physical exercise programs associated with nutrition education, lasting 3 months, from November 7 to January 7, 2014. 30 obese sedentary workers 44 ± 844 ± 8.6 on average, year-olds were randomly selected from 157 obese individuals out of a general population of 400 employees in the personal list of the selected company. These workers were divided into three groups of physical exercises, of which the first group consisted of 10 workers in a three-day, moderate to high intensity structured exercise program, including: jogging, aerobics, basketball, volleyball, swimming, abdominals and walking of 10,000 steps a day. The second group was also composed of 10 workers undergoing a spontaneous exercise program of the same duration, intensity and frequency including: walk, up and down the stairs and finally the third group composed and then the third group of 10 workers submitted to a mixed exercise program (the mixture of the two programs). Quantitative variables were expressed as mean ± standard deviation. The ANOVA test was used to compare the variables of two groups. A value of p-value ≤ 0.05 was considered a threshold of statistical significance. Decreased weight, waist circumference and body mass index were observed intra group before and after exercise programs. After the intervention, the group subjected to the mixed exercises improved more significantly (p = 0.0001) the morphological parameters of the obese than the group subjected to the structured and spontaneous exercises with diet. A moderate to high intensity, high volume mixed exercise program significantly improves the morphology of obese sedentary workers compared to the structured and spontaneous exercise program. It can be considered as an effective non-pharmacological strategy to combat the nutritional and epidemiological transition in the workplace, where obesity is the main cornerstone.